KONTRIBUSI BIMBINGAN DAN KONSELING KARIR DALAM MENUMBUHKAN SIKAP KEWIRAUSAHAAN SISWA DI KOTA TERNATE - Hasrul, Hasrul; Arif, Nutfah A.M; Ahmad, Hariadi (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
Career guidance and counseling have an important role in school programs that aim to stimulate and facilitate students’ career development, including fostering attitudes and interest in the field of entrepreneurship. This article aims to conceptually describe the contribution of career guidance and counseling services in the form of scientific publications as an effort to foster students' entrepreneurial attitudes in Ternate City. The research method used is a narrative literature review (NRL). The results of the research show that in the last five years, there has been no contribution from career guidance and counseling services in fostering entrepreneurial attitudes for elementary to middle school students in Ternate City which have been published in the form of reputable scientific journals. Another finding is that the contribution of career guidance and counseling services using various techniques is effective in fostering students’ entrepreneurial attitudes, especially at the secondary school level in several regions in Indonesia, however, the number of publications in the form of scientific journals is still very minimal.